Evaluating anticancer activity of emodin by enhancing antioxidant activities and affecting PKC/ADAMTS4 pathway in thioacetamide-induced hepatocellular carcinoma in rats - Hanan M. Hassan; Ahmed M. Hamdan; Abdullah Alattar; Reem Alshaman; Omar Bahattab; Mohammed M. H. Al-Gayyar (Redox Report)
Emodin is a naturally occurring anthraquinone derivative with a wide range of pharmacological activities, including neuroprotective and anti-inflammatory activities. We aim to assess the anticancer activity of emodin against hepatocellular carcinoma (HCC) in rat models using the proliferation, invasion, and angiogenesis biomarkers. After induction of HCC, assessment of the liver impairment and the histopathology of liver sections were investigated. Hepatic expression of both mRNA and protein of the oxidative stress biomarkers, HO-1, Nrf2; the mitogenic activation biomarkers, ERK5, PKCδ; the tissue destruction biomarker, ADAMTS4; the tissue homeostasis biomarker, aggregan; the cellular fibrinolytic biomarker, MMP3; and of the cellular angiogenesis biomarker, VEGF were measured. Emodin increased the survival percentage and reduced the number of hepatic nodules compared to the HCC group. Besides, emodin reduced the elevated expression of both mRNA and proteins of all PKC, ERK5, ADAMTS4, MMP3, and VEGF compared with the HCC group. On the other hand, emodin increased the expression of mRNA and proteins of Nrf2, HO-1, and aggrecan compared with the HCC group. Therefore, emodin is a promising anticancer agent against HCC preventing the cancer prognosis and infiltration. It works through many mechanisms of action, such as blocking oxidative stress, proliferation, invasion, and angiogenesis.